Pemanfaatan Lahan Pekarangan di Sekolah Sungai Ciliwung Jakarta untuk Tanaman Buah-Buahan - Hinijati Widjaja; Rini Fitri; Reza Fauzi; Harmaini Harmaini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Ciliwung River School Yard Jakarta management is still natural and dominated by similar ornamental plants. Lack of knowledge and skills of partners regarding using their yards for planting fruit trees can increase economic value and reforestation. This program aims to improve knowledge and skills in cultivating fruit trees on the grounds of the Ciliwung river school in Jakarta. The method used in implementing this community service is through the stages of program socialization, counseling and demonstrations, planting fruit trees in the pilot garden of the Ciliwung River School. The results obtained with this counseling can help partners increase their knowledge and information about using yards for productive and economical fruit tree plants.